Determinants of In-Hospital Mortality Following Pelvic Ring Fractures: A 4.5-Year Analysis from a Developing Country's Trauma Center - Jaya Ndaru Prasetio; Ismail Bastomi; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Pelvic ring fractures are calamitous injuries with high mortality. While clinical risk factors are well-defined in high-income countries, there is a scarcity of data from low- and middle-income countries (LMICs), where socioeconomic factors may critically influence survival. This study sought to explore the sociodemographic and clinical factors associated with in-hospital mortality following pelvic fractures at a tertiary trauma center in Indonesia. Methods: A retrospective cohort study was performed on all patients (N=31) admitted with traumatic pelvic fractures to Dr. Mohammad Hoesin General Hospital between January 2021 and June 2025. Data on patient demographics, socioeconomic variables, injury mechanisms, and clinical management were analyzed. The primary outcome was in-hospital mortality. Given the exploratory nature of the study and the small sample size, bivariate analysis using Pearson's Chi-Square and Fisher’s Exact tests was conducted to identify potential associations. Results: The overall in-hospital mortality rate was 9.7% (3 of 31 patients). The cohort was primarily young adults (61.3% aged 20-59 years) injured in traffic accidents (87.1%). The only variable found to have a statistically significant association with mortality was occupation. All three fatalities occurred in patients from the informal employment sector, corresponding to a 37.5% mortality rate within this subgroup (p=0.008). No significant association was found for established clinical predictors, including Young-Burgess fracture classification (p=0.736), a finding likely attributable to the study's limited statistical power. Conclusion: This study, though limited by its sample size, identified a powerful association between informal sector employment and mortality after pelvic fracture. This finding generates the critical hypothesis that in an LMIC setting, socioeconomic vulnerability is a paramount driver of poor outcomes, likely mediated through delays in care and presentation with more severe physiological derangement. These results underscore the need for a socio-clinical approach to trauma care and highlight a crucial area for future, more definitive research.